Factors affecting intention to use of online installment payment Paylater - Ivonanda Nindya; Rifelly Dewi Astuti (President University, 2022)
Mobile wallets do offer a variety of attractive features and offers, for example a payment method that users can choose from, such as installment payment called paylater. In recent years, internet-based installment methods have become increasingly popular with users of e-commerce and services on mobile devices Currently in Indonesia there are several digital wallet companies that provide paylater payment features such as Shopeepay, OVO, and Go-pay. Both manufacturing and financial services develop technological innovations not only to provide benefits for their consumers, but also to expand their business fields. In other words, the benefits of mobile payment services (MPs) are not only to provide added value for consumers but also to provide marketers with wider access to consumer consumption data on mobile platforms. Therefore, it is important to look at the process that takes place before consumers adopt the use of paylater as a payment method. This research will be entered into a descriptive study using a cross-sectional study to answer research questions. This study aims to identify factors that influence usage intention of paylater services through a model from the diffusion of innovation theory and obtained answers from 211 respondents through online questionnaires. Results revealed that compatibility and trialability were positively associated with participants’ intention to use paylater. However, low complexity had no association with participants’ intentions to use paylater.